Deformações ao longo do tempo de geossintéticos aplicados a uma estrutura de solo reforçado - Goulart, João Maurício Homsi (2018)
In service, excessive deformations can lead a geossynthetic soil reinforced structure to failure or undermine it under operational condition. In the design, usually, because of the uncertainly of the long-term efforts, reduction factors are applied, misleading (most of time) to an over conservative design. Among the efforts, there are polymeric reinforcement material creep and whole composition (soil-reinforcement) long-term deformations. In relation to time-dependent behavior, most literature works investigate the long-term behavior with laboratory confined and unconfined tests, few are with real structure captured data. In this context, the present study investigated the long-term behavior of a wall, reinforced with geogrids and woven geotextiles, with a long-term deformations approach. The studied wall was built with local fine soil. The field monitoring collected data was from execution and about to 10.000 hours under operation. The instrumentation consisted in mechanical extensometers to capture internal displacements and topographic surveys to capture settlements. Thus, there was laboratorial approach of the time-dependent reinforcement creep behavior with non-confined test, to compare to observed field behavior. The results shown the long-term deformations are up to 50% of the peak constructive deformation, field versus laboratory comparisons shown that long-term deformations tendency in laboratory underestimated the field. The Sherby-Dorn plots exhibit low creep rates, indicating the reinforcements are in the primary creep, corroborating with literature that, low loads in reinforcements under operation, leads to negligible long-term deformations.